2013
DOI: 10.1680/gmat.12.00014
|View full text |Cite
|
Sign up to set email alerts
|

Greener, cleaner polymerization of isobutene

Abstract: Methylaluminoxane (MAO)/silyl halide-based initiator systems greatly improve the sustainability of isobutene (IB)polymerizations by eliminating halogenated solvents, reducing energy consumption and removing the need for postpolymerization purifi cation. These solvent-free systems give rise to moderate yields of high-molecular-weight (MW) polymers at convenient temperatures without conventional toxic solvents. In addition, facile separation of MAO and polyisobutene (PIB) was accomplished with supported MAOs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Benchtop scale reactions showed that the polymerization of neat IB with supported SSMAO in conjunction with a carbocation synthon could proceed with explosive violence. 22 The rate at which polymerization occurred at ambient T to give high conversion was directly related to the propensity for the carbocation synthon to undergo ionization and found to decline as follows 1,4-dicumyl chloride (∼1−2 s) > 2-bromobutane (∼5−10 s) > ethyl bromide (∼5−10 min) > dichloromethane (∼2−3 h) > chloroform (∼10−12 h). 13 Identical polymerization runs in n-hexane were found to be more controllable, and of the aforementioned initiators, 2-BrBu had the most favorable degree of activity, effecting full conversion within 1 h once the proper ratio of the coinitiator to initiator was determined (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Benchtop scale reactions showed that the polymerization of neat IB with supported SSMAO in conjunction with a carbocation synthon could proceed with explosive violence. 22 The rate at which polymerization occurred at ambient T to give high conversion was directly related to the propensity for the carbocation synthon to undergo ionization and found to decline as follows 1,4-dicumyl chloride (∼1−2 s) > 2-bromobutane (∼5−10 s) > ethyl bromide (∼5−10 min) > dichloromethane (∼2−3 h) > chloroform (∼10−12 h). 13 Identical polymerization runs in n-hexane were found to be more controllable, and of the aforementioned initiators, 2-BrBu had the most favorable degree of activity, effecting full conversion within 1 h once the proper ratio of the coinitiator to initiator was determined (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The synthesis of silica-supported MAO was carried out in a manner similar to that described by Jacobsen et al 25 and is detailed in a previous publication by this research group. 22 This involves the reaction of calcined Davison Grade 11 silica gel (28−200 mesh) with a toluene solution of MAO, followed by the removal of volatiles under reduced pressure with heating. Although no issues were encountered in the preparation of this material, it should only be attempted by trained professionals.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…HPAs have been used as initiators of cationic polymerization; however, their MW‐T profiles are substandard, and they are not cost competitive to traditional LAs (e.g., BF 3 ) . As part of earlier investigations on supported methylaluminoxane and heterogeneous PFLA based initiator systems, we also studied activated forms of HPAs as solid acid initiators with limited success…”
Section: Introductionmentioning
confidence: 99%